Phase formation behavior of perovskite ferroelectric lead zirconate titanate - lead zinc niobate powders by X-ray absorption spectroscopy - Kanchiang K. (2017)
© 2016 Taylor & Francis Group, LLC. Lead zirconate titanate - lead zinc niobate (PZT-PZN) powders were prepared by a modified mixed-oxide synthetic route via a combination of Zn 2 Nb 34 O 87  precursor and vibro-milling techniques. The effects of calcination temperature and chemical composition on phase formation were investigated by x-ray absorption spectroscopy. The Zn K-edge x-ray absorption near edge structure (XANES) was simulated with PZT-PZN in pyrochlore phase and perovskite phase. The comparison between simulated and measured XANES shows the increasing perovskite phase formation of PZT-PZN with increasing calcination temperature and the optimization of calcination temperature lead to 100% yield of PZT-PZN in perovskite phase. In addition, the Zn K-edge x-ray absorption near edge structure (XANES) was simulated with various compositions of PZT in PZT-PZN. The comparison between simulated and measured XANES shows the increasing perovskite phase formation of PZT-PZN with increasing composition of PZT. The results show the optimization of calcination conditions lead to formation of PZT-PZN in perovskite phase.